Hidden barriers to safe childbirth: Female genital cutting and facility-based delivery in Nigeria - Josephine Aikpitanyi; Justinah Bamikole; Goodnews Daniel; Hope Egharevba (Utan Kayu Publishing, 2026)
Female genital cutting (FGC) remains a persistent public health and human rights concern, yet its implications for maternal healthcare utilisation are less well understood. This study examines the association between FGC and facility-based delivery in Nigeria using nationally representative data from the 2021 Multiple Indicator Cluster Survey. Guided by a conceptual framework linking sociocultural practices to healthcare utilisation, we analysed data from 10,008 women aged 15–49 who had a live birth within two years preceding the survey. Survey-weighted descriptive statistics, logistic regression models, and average marginal effects were used, with a robustness check based on modified Poisson regression. Approximately 27% of women reported having undergone FGC. While unadjusted differences in facility-based delivery were small, multivariable results showed that women with FGC were less likely to deliver in a health facility (AOR = 0.62; 95% CI: 0.45–0.86). The average marginal effect indicated a 6.7 percentage-point lower probability of facility-based delivery, equivalent to about 7 fewer facility births per 100 deliveries. These findings suggest that FGC is associated with reduced utilisation of institutional childbirth services, highlighting the need for culturally responsive maternity care and integrated interventions that address both access and sociocultural barriers to improve maternal health outcomes. Abstrak. Praktik pemotongan genital perempuan (FGC) masih menjadi isu kesehatan masyarakat dan hak asasi manusia yang signifikan, namun dampaknya terhadap pemanfaatan layanan kesehatan maternal belum sepenuhnya dipahami. Penelitian ini bertujuan untuk menganalisis hubungan antara FGC dan persalinan di fasilitas kesehatan di Nigeria menggunakan data representatif nasional dari Multiple Indicator Cluster Survey tahun 2021. Berdasarkan kerangka konseptual yang mengaitkan praktik sosial budaya dengan pemanfaatan layanan kesehatan, penelitian ini menganalisis data dari 10.008 perempuan usia 15–49 tahun yang melahirkan dalam 2 tahun sebelum survei. Analisis dilakukan menggunakan statistik deskriptif berbobot, regresi logistik, serta average marginal effects, dengan uji ketahanan menggunakan regresi Poisson termodifikasi. Sekitar 27% responden melaporkan telah mengalami FGC. Meskipun perbedaan tidak teradjust relatif kecil, hasil multivariat menunjukkan bahwa perempuan dengan FGC memiliki kemungkinan lebih rendah untuk melahirkan di fasilitas kesehatan (AOR = 0,62; 95% CI: 0,45–0,86). Efek marginal menunjukkan penurunan probabilitas sebesar 6,7 poin persentase, setara dengan sekitar 7 persalinan di fasilitas per 100 kelahiran. Temuan ini menunjukkan bahwa FGC berkaitan dengan rendahnya pemanfaatan layanan persalinan di fasilitas kesehatan, sehingga diperlukan pendekatan pelayanan maternal yang sensitif secara budaya serta intervensi terpadu untuk mengatasi hambatan akses dan hambatan sosial budaya guna meningkatkan hasil kesehatan ibu.